Markovian channel modeling for multipath mitigation in navigation receivers - Krach, Bernhard; Weigel, Robert (European Conference on Antennas and Propagation, 2009)
Multipath is today still one of the most crucial problems in satellite navigation, in particular in urban environments, where the received navigation signals can be affected by blockage, shadowing and multipath reception. Latest multipath mitigation algorithms are based on the concept of sequential Bayesian estimation and improve the receiver performance by exploiting the temporal constraints of the channel dynamics, which have to be characterized by a first-order Markovian model for this purpose. In this paper such a channel model is introduced. Simulation results show the benefit of the novel model.
elib2cris::1512001600,krach2009
Keywords: Markovian channel modeling; multipath mitigation; navigation receivers; satellite navigation; sequential Bayesian estimation; Markov processes; satellite navigation